The Use of Short, Animated, Patient-Centered Springboard Videos to Underscore the Clinical Relevance of Preclinical Medical Student Education. (July 2017) - Adam, Maya; Chen, Sharon F.; Amieva, Manuel; Deitz, Jennifer; Jang, Heeju; Porwal, Aarti; Prober, Charles
Abstract : Problem: Medical students often struggle to appreciate the clinical relevance of material taught in the preclinical years. The authors believe videos could be effectively used to interweave a patient's illness script with foundational basic science concepts. Approach: In collaboration with four other U.S. medical schools, educators at the Stanford University School of Medicine created 36 short, animated, patient-centered springboard videos (third-person, narrated accounts of authentic patient cases conveying foundational pathophysiology) in 2014. The videos were used to introduce students to 36 content modules, created as part of a microbiology, immunology, and infectious diseases curriculum. The videos were created with input from faculty content experts and in some cases medical students, and were piloted using a flipped classroom pedagogical approach in January 2015–June 2016. Outcomes: Student feedback from course evaluations and focus groups was analyzed using a mixed-methods approach. On the course evaluations, the majority of students rated the patient-centered videos positively, and the majority of comments on the videos were positive, highlighting both enhanced engagement and enhanced learning and retention. Comments from focus groups mirrored the course evaluation comments and highlighted different usage patterns for the videos. Next Steps: The authors will continue to gather and analyze data from schools using the videos as part of their core preclinical curriculum, and will produce similar videos for use in other areas of undergraduate medical education. These videos could support students' review of content taught previously and be repurposed for use in continuing and graduate medical education, as well as patient education. Abstract : Supplemental Digital Content is available in the text.